2(4x+7)=2x-4
distribute
8x+14=2x-4
-2x from feach side
6x+14=-4
-14 from each side
6x=-18
divide by 6
x=-3
and the next one
-2(18-3y)=7y+2y
distribue and add light terms
-36+6y=9y
subtract 6y from each side
-36=3y
divide by 3
-12=y
:) welcome
2006-11-13 11:01:55
·
answer #1
·
answered by Samz 2
·
0⤊
0⤋
1) 2(4X+7) = 2X-4
8X+14 = 2X-4
6X=-18
X=-3
2) -2(18-3Y) = 7Y+2Y
-36+6Y=9Y
-36 = 3Y
-12 = Y OR Y = -12
2006-11-13 19:01:57
·
answer #2
·
answered by tdbhc33 2
·
0⤊
0⤋
1. 8 x +14 = 2 x-4
subtract 2 x from both sides and 14 from both sides
8x-2x = -4-14
6x = -18
6x/6 = -18/6
x= -3
2. -36+6 y = 7 y+2y
-36 +6y = 9 y
-36=9y-6y
-36 = 3y
-12 = y
2006-11-13 19:04:08
·
answer #3
·
answered by shaft0208 1
·
0⤊
0⤋
2(4x+7)=2x-4
8x + 14 = 2x - 4
6x = -18
x = -3
-2(18 - 3y)=7y+2y
-36 + 6y = 9y
-36 = 3y
y = -12
2006-11-13 19:02:45
·
answer #4
·
answered by trackstarr59 3
·
0⤊
0⤋
2(4x+7)=2x-4 8x+14=2x-4 8x-2x=-14-4 6x=-18
x=3
-2(18-3y)=7y+2y -36+6y=9y 6y-9y=36 -3y=36
y=-12
2006-11-13 19:04:21
·
answer #5
·
answered by Rex 4
·
0⤊
0⤋
I'll tell you what to do to solve 1 the other one just follow the steps and you should be able to do it yoursef.
2(4x+7)=2x-4
First you have to get the parenthesis out so you multiply by 2 what's inside and get:
8x+14=2x-4
Then you put the numbers together with the numbers and the letters with the letters and you get:
8x-2x=-4-14
Manipulating you get that:
6x=-18
Then you divide both sides by the number next to the variable and you get that
x=-6
Notice that it can be a negative number
2006-11-13 19:02:26
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
* Before you distribute, the first equation has "2" as a common factor. So divide by 2 to get 4x + 7 = x - 2.
* Always check your work by plugging x and y back into both equations.
* The first answer is not always the best.
2006-11-13 19:09:24
·
answer #7
·
answered by emilynghiem 5
·
0⤊
0⤋
2(4x+7)=2x-4
x=-3
for the second one y=-12
2006-11-13 18:59:35
·
answer #8
·
answered by poipman1 3
·
0⤊
0⤋
4x+7=x-2
3x=-9
x= -3
-38+6y=9y
-38=3y
y= -38/3
2006-11-13 19:00:34
·
answer #9
·
answered by 7
·
0⤊
0⤋
x=-3
y=-12
2(4x+7)=2x-4
8x+14=2x-4
6x=-18
x=-3
-2(18-3y)=7y+27
-36+6y=9y
-36=3y
-12=y
2006-11-13 19:03:33
·
answer #10
·
answered by N P 1
·
0⤊
0⤋